13-(-9x)+3x-(-11)=

Simple and best practice solution for 13-(-9x)+3x-(-11)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-(-9x)+3x-(-11)= equation:


Simplifying
13 + -1(-9x) + 3x + -1(-11) = 0

Remove parenthesis around (-9x)
13 + -1 * -9x + 3x + -1(-11) = 0

Multiply -1 * -9
13 + 9x + 3x + -1(-11) = 0

Multiply -1 * -11
13 + 9x + 3x + 11 = 0

Reorder the terms:
13 + 11 + 9x + 3x = 0

Combine like terms: 13 + 11 = 24
24 + 9x + 3x = 0

Combine like terms: 9x + 3x = 12x
24 + 12x = 0

Solving
24 + 12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 12x = 0 + -24

Combine like terms: 24 + -24 = 0
0 + 12x = 0 + -24
12x = 0 + -24

Combine like terms: 0 + -24 = -24
12x = -24

Divide each side by '12'.
x = -2

Simplifying
x = -2

See similar equations:

| 9-2x=9-7x | | 7m^2-28m-224=0 | | 2b-4-9b-9= | | x-0.5x-0.75x-0.5x=200 | | 8/27+1/9+4/9= | | 5x^4*2x^3= | | 0=-4x^2+24x+12 | | 9(n+2)+8n+7= | | .25+.6(50-m)=0 | | 15a^2-3ab-18b^2=0 | | 3x^2+12=66 | | 4v-8=4v-12 | | 1+6y-16y= | | 3x-19x= | | -3y+2=10y+30 | | 2z+.6=3z+.2 | | f(x)=-x^4+x^2 | | 26-2x=10+6x | | 7(18-x)-6(3-5x)=-(7x+9)-3(2x+5) | | 18(x+18)=21squared | | 2x+.6=3z+.2 | | f(x)=5x^3+7x^2-x+9 | | 1x=-1x-8 | | 4x+3-2x=33 | | 2n+5=-n-13 | | 6m=2344 | | 0.5x+.35(30)=24.5 | | 6.5p+4a=6 | | .4x+.6=-.6 | | 72=24y | | -4x^2+7x+36=0 | | 8x+8-20=5y-4y |

Equations solver categories